2021
DOI: 10.29252/ijrr.19.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a bystander effect after therapeutic ultrasound exposure in human melanoma: In-vitro assay

Abstract: Induction of a bystander effect after therapeutic ultrasound exposure in human melanoma: In-vitro assay INTRODUCTIONIt is well established that radiation can induce cellular responses in non-irradiated cells which are termed radiation-induced bystander effect (RIBE) (1) . This phenomenon leads to radiation induced-injuries in non-irradiated bystander cells. As reported, non-irradiated cells show a variety of biological responses, including reduced viability fraction (2) , chromosomal instability (3) , DNA doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, Hao et al reported a viability value of 62% for C6 glioma cells upon UW exposure at 1.0 W cm -2 and 1.0 MHz for one minute [ 38 ]. Another study showed that the A375 cell-killing ability of UW depended on the time of exposure [ 39 ]. It can be decided that the biocompatibility of UW depends on the cell type, and exposure conditions of time, intensity, and frequency [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Hao et al reported a viability value of 62% for C6 glioma cells upon UW exposure at 1.0 W cm -2 and 1.0 MHz for one minute [ 38 ]. Another study showed that the A375 cell-killing ability of UW depended on the time of exposure [ 39 ]. It can be decided that the biocompatibility of UW depends on the cell type, and exposure conditions of time, intensity, and frequency [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies show the potential of ionizing radiations such as X and gamma rays [ 8 ] or even chemotherapy agents [ 9 ] for inducing the bystander effect but a few studies investigated safer cancer treatment modalities such as therapeutic ultrasound (US) in creating this effect [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%